Quality of soil from the nickel mining area of Southeast Sulawesi, Indonesia, engineered using earthworms (Pheretima sp.) - Hasbullah Syaf; Muhammad Albar Pattah; Laode Muhammad Harjoni Kilowasid (Journal of Degraded and Mining Lands Management, 2021)
Earthworms (Pheretima sp.) could survive under abiotic stress soil conditions. Furthermore, their activities as ecosystem engineers allow for the creation of soil biostructures with new characteristics. Therefore, this study aimed to investigate the effect of the abundance of Pheretima sp. on the aggregate size, physicochemistry, and biology of the topsoil from the nickel mining area of Southeast Sulawesi, Indonesia. It was carried out by first grouping their abundance into zero, two, four, six, and eight individuals per pot and then carrying out tests. The Pheretima sp. were then released onto the surface of the topsoil and mixed with biochar that was saturated with tap water in the pot overnight. The results showed that the abundance of the species had a significant effect on the size class distribution, and aggregate stability of the soil. Furthermore, the size of the soil aggregates formed was dominated by the size class 2.83 - 4.75 mm under both dry and wet conditions. Under dry conditions, three size classes were found, while under wet conditions, there were five size classes. The results also showed that the highest and lowest stability indexes occurred with zero and eight Pheretima sp., respectively. Furthermore, the abundance had a significant effect on pH, organic C, total N, CEC, and total nematodes. However, it had no significant effect on the total P, C/N ratio, total AMF spores, and flagellate. The highest soil pH occurred with zero Pheretima sp., while with six and two members of the species, the total nematode was at its highest and lowest populations, respectively. Therefore, it could be concluded that the species was able to create novel conditions in the topsoils at the nickel mining area that were suitable for various soil biota.